Bridging Cultures and Meaning: EFL Learners’ Challenges in Translating English Idiomatic Expressions - Eka Fanti Sulistiyaningsih; Zulfa Nabila; Endang Susilowati; Etika Dewi Kusumaningtyas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Translation is essential in English as a Foreign Language (EFL) education, particularly in helping learners understand and express meaning across languages. This study aims to explore the challenges faced by EFL learners in translating English idiomatic expressions and to examine the linguistic and cultural factors underlying these challenges. This study adopts a qualitative descriptive research design with limited quantitative support. The researcher used error analysis and content analysis to analyze the data to answer the first research question. Then, the researcher used thematic analysis to analyze the data from the questionnaire and interview to answer the second research question. The participants of this study are EFL learners studying English as a foreign language at a university level in Central Java. The instruments used in this study are the idiomatic translation test, questionnaire, and interview. The researcher found that the challenges faced by EFL learners in translating English idiomatic expressions were lexical challenge (18%), semantic challenge (36%), idiomatic challenge (14%), and literal translation tendencies (32%). Then, the researcher found linguistic factors contribute to EFL learners’ difficulties in translating English idiomatic expressions accurately, such as vocabulary (45%), idiom familirity (35%), and grammar (20%). On the other hand, the researcher found that cultural factors contribute to EFL learners’ difficulties in translating English idiomatic expressions accurately, such as cultural references (40%), context (30%), and figurative meaning (30%). This study highlights the need for greater emphasis on idiomatic competence, cultural awareness, and contextual understanding in EFL instruction